The coffin of an anonymous woman from Bab El Gasus (A.4) in Sociedade de Geografia de Lisboa - Sousa, Rogério (2010)
The coffin discussed in this article was found in 1891 in the main corridor of Bab el-Gasus, the collective tomb of the priests of Amun in Deir el-Bahari, just at its entrance, thus being in close proximity with the shaft. The coffin integrated the lot of antiquities presented to Portugal in 1893 by the Egyptian authorities. This lot consisted of 188 shabtis, one outer anthropoid coffin, four inner anthropoid coffins, and three mummy-covers. All these objects were given to the Sociedade de Geografia de Lisboa where they still remain today. Although not particularly luxurious or exceptional either on its decoration or craftsmanship, nevertheless the anthropoid coffin A.4 presents us some interesting questions related to the social and material context that evolved the production of the funerary art in the late 21st Dynasty.